Isoform isolation crotalin C2 obtained from Crotalus durissus terrificus venom totals - Ronald Demetrio Navarro Oviedo (2017)
Three crotamine isoforms (C1, C2 y C3) were obtained from venom Peruvian, Madre de Dios, Crotalus durissus terrificus after a single of molecular exclusion chromatography coupled to HPLC. The major isoform was C2.